Gambling disorder duration and cognitive behavioural therapy outcome considering gambling preference and sex - Lucas, Ignacio; Granero, Roser; Fernández-Aranda, Fernando; Solé-Morata, Neus; Demetrovics, Zsolt; Baenas, Isabel; Gómez-Peña, Mónica; Moragas, Laura; Mora-Maltas, Bernat; Lara-Huallipe, Milagros Lizbeth; Jiménez-Murcia, Susana (Journal of psychiatric research, 2023)
Gambling Disorder (GD) is a behavioural addiction that leads to high level of clinical distress and, in general, it is characterized by enduring symptomatology that presents high rates of chronicity. However, there is high variability of illness duration among patients who seek treatment for GD. Previous studies reported mixed results about the relevance of illness duration in GD treatment outcome. However, there are different profiles of patients who are diagnosed with GD. For this reason, this study aimed to evaluate the effect of illness duration in the treatment outcome of different profiles of GD patients according to their gambling preference and sex. The sample were 1699 patients diagnosed with GD. All patients received cognitive-behavioural therapy in a group format. Treatment outcome was evaluated in terms of relapsing to gambling behaviours and dropout from treatment. Results showed higher probability of poor outcome in the first years of the disorder for strategic gambling compared to non-strategic or mixed forms of gambling. Moreover, women also showed higher probability of poor outcomes than men since the first stages of the disorder. This study draws attention to the relevance of illness duration in the treatment outcome of specific profiles of GD patients. In particular, patients who presented a preference for strategic forms of gambling and women who are diagnosed with GD would have a higher risk of poor treatment outcomes since the first stages of the disorder. These results highlight the importance of an early intervention in these patients in order to prevent the chronicity of the disorder.